2010
DOI: 10.1002/jbm.a.32852
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of foreign body response on polyurethane by surface entrapment technique

Abstract: Implanted polymeric materials, such as medical devices, provoke the body to initiate an inflammatory reaction, known as the foreign body response (FBR), which causes several complications. In this study, polyurethane (Tecoflex®, PU) surface modified with the nonionic surfactant Tween80® (PU/T80) and the cell adhesive PLL-RGD peptide (PU/PLL-RGD) by a previously described entrapment technique were implanted in the peritoneal cavity of Wistar rats for 30 days. Implants were retrieved and examined for tissue reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…Similarly, promoting transient shifts in macrophage polarization in the early host response represents an improved approach as compared to strategies which seek to evade the host immune response. Previous studies using surface modification of biomaterials and coatings to escape the innate immune system have shown only modest improvements at early stages of the host response against biomaterials and few improvements in long-term performance [56-60]. Finally, the present delivery system represents an advantage over previous delivery approaches, given that significant effects on macrophage polarization are observed at lower, controllable and safer doses (picograms to nanograms), compared to the high doses (nanograms to micrograms) of IL-4 used in previous studies [19, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, promoting transient shifts in macrophage polarization in the early host response represents an improved approach as compared to strategies which seek to evade the host immune response. Previous studies using surface modification of biomaterials and coatings to escape the innate immune system have shown only modest improvements at early stages of the host response against biomaterials and few improvements in long-term performance [56-60]. Finally, the present delivery system represents an advantage over previous delivery approaches, given that significant effects on macrophage polarization are observed at lower, controllable and safer doses (picograms to nanograms), compared to the high doses (nanograms to micrograms) of IL-4 used in previous studies [19, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…As we already know from in vitro results that the surface plays a very important role in the bio-compatibility of polyurethanes, is it also true for in vivo ? The answer is yes according to Khandwekar's research, which demonstrated that surface entrapment technique could be used to modify/control the foreign body response on polyurethane surfaces (Khandwekar et al, 2010). Besides the basic research, a lot of polyurethane based medical devices were prepared and placed into animals for in vivo tests, which will be discussed below.…”
Section: Biocompatibility Evaluationmentioning
confidence: 99%
“…The dramatic decrease in contact angle suggests that hydrophilic PEG was indeed coated on the surface of the nanofibers. Compared with other surface modification methods, the result was better than plasma treatment (around 50 ) 42 and surface grafting with acrylic acid (40)(41)(42)(43)(44)(45) ). 43 The resultant hydrophilicity is crucial for future applications as biomedical materials.…”
Section: Resultsmentioning
confidence: 97%
“…This method can also be applied for surface engineering of other polymers, for example, polypropylene 39 and polyurethane. 40,41 After surface entrapment at 42 C, the PDLLA nanofiber mats shrunk to approximately 25% of their original size. Then the nonwoven mats were cut into 10 mm  10 mm specimens and immersed in Tris buffer at 37 C. Their size was measured at each time interval.…”
Section: Resultsmentioning
confidence: 99%